Extracellular Vesicles as Tools for Crossing the Blood–Brain Barrier to Treat Lysosomal Storage Diseases - Giovanni Lerussi; Verónica Villagrasa-Araya; Marc Moltó-Abad; Mireia del Toro; Guillem Pintos-Morell; Joaquin Seras-Franzoso; Ibane Abasolo (Life)
Extracellular vesicles (EVs) are nanosized, membrane-bound structures that have emerged as promising tools for drug delivery, especially in the treatment of lysosomal storage disorders (LSDs) with central nervous system (CNS) involvement. This review highlights the unique properties of EVs, such as their biocompatibility, capacity to cross the blood–brain barrier (BBB), and potential for therapeutic cargo loading, including that of enzymes and genetic material. Current therapies for LSDs, like enzyme replacement therapy (ERT), often fail to address neurological symptoms due to their inability to cross the BBB. EVs offer a viable alternative, allowing for targeted delivery to the CNS and improving therapeutic outcomes. We discuss recent advancements in the engineering and modification of EVs to enhance targeting, circulation time and cargo stability, and provide a detailed overview of their application in LSDs, such as Gaucher and Fabry diseases, and Sanfilippo syndrome. Despite their potential, challenges remain in scaling production, ensuring isolation purity, and meeting regulatory requirements. Future developments will focus on overcoming these barriers, paving the way for the clinical translation of EV-based therapies in LSDs and other CNS disorders.